Relationship between Metabolic Syndrome and Mediterranean Diet in Adolescents: A Cross-Sectional Study: Metabolic Syndrome and Mediterranean Diet - Çağıran Yılmaz, Feray (Progress in Nutrition, 2021)
Objectives: The objective of the present study is to investigate the relationship between Metabolic Syndrome (MetS) and Mediterranean Diet in adolescents. Methods: This cross sectional study included 367 adolescents who visited Primary Health Service Centers in 7 cities in Turkey. Participants’ biochemical parameters, anthropometric measurements and blood pressures were measured. The level of adherence to Mediterranean Diet was evaluated by a clinical questionnaire, the Mediterranean Diet Quality Index for children and adolescents (KIDMED). Results: A poor adherence to Mediterranean diet was seen in 31,9% of subjects, while 68,1% had a medium-high compliance. In total, 51,2% adolescents with MetS had poor adherence to a Mediterranean diet. Although the data were not statistically significant, most of the participants with metabolic syndrome physically inactive and skipped meals. In this study the prevalence of MetS was 21,8%. IFG, hypertension and abdominal obesity were more frequent in girls compared to boys (p<0,001). A poor adherence to Mediterranean diet group showed the highest level of triglycerides level when compared with those with medium-high adherence to a Mediterranean diet. Conclusions: A poor adherence to Mediterranean diet is associated with MetS. Results support the need to engage adolescents in regular physical activity and adherence to the Mediterranean diet.